Bulletin 75 Rules and Regulations for Metal Mines - W. R. Ingalls; James Douglas; J. R. Finlay; J. PARKE CHAN- NING; John Hays Hammond (The National Institute for Occupational Safety and Health (NIOSH), 1915)
The committee making this report, consisting of Walter Renton Ingalls (chairman), J. Parke Channing, James Douglas, James R. Finlay, and John Hays Hammond, was originally appointed at a meeting of the American Mining Congress at Denver, Colo., in No- vember, 1906. The object of this appointment was the drafting of a modern law governing quarrying and metalliferous mining which could be recommended to the several States for adoption, in the hope that the passage of such a uniform law by the mining States would tend to lower the number of fatal and serious accidents. The first step of the committee (the personnel of which has re- mained unchanged from the beginning) was to procure copies of existing laws from the officials of the several States of the Union. With the assistance of the Engineering and Mining Journal, copies of the laws of Great Britain, the Transvaal, New South Wales, Victoria, Queensland, Western Australia, Tasmania, New Zealand, and certain European countries were also obtained. The replies to the inquiries made at that time developed the fact that a number of States in which mining was carried on had no laws at all. Other States were found to have elaborate provisions regulating coal min- ing, but none applying to metalliferous mining. Still other States were found to have miscellaneous and unrelated provisions passed at odd times, seemingly as the result of the occurrence of some dis- aster or other.